Distal Hypospadias, Treated or Untreated?: A Case Report - Santosa, Agus (Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Background: Treatment for distal hypospadias is a controversy among the experts. Some argue that it does not require any surgery if it does not interfere with the patient's urinary and sexuality. Purpose: This study aimed to determine whether patients with distal hypospadias need treated or untreated.Methods: The method used is a case study. Participants in this study is a 10-year-old male with distal hypospadias—location of the study in Purwokerto city, Banyumas district, Central Java. Participants were interviewed and physically examined by a doctor and nurse. The results of interviews and physical examinations are recorded and analyzed based on a literature review to determine the decision, treatment, or untreated. Results: A 10-year-old patient with hypospadias and the pediatric urologist do not give surgery advice, because the urethral opening is still close to the glans penis, and there are no symptoms of urinary dysfunction. Conclusion: Patients with distal hypospadias may be untreated as long as they do not interfere with urinary function